Implementation and emulation of adaptive-array algorithms for direct-sequence systems - Calomiris, T. J.; Torrieri, D.; Gwyn, D. A.; Ziyaee, T. (2011 - MILCOM 2011 Military Communications Conference, 2011)
The maximin algorithm is a blind adaptive-array algorithm that suppresses interference and thereby supplements the inherent processing gain of a spread-spectrum system. The ISPA algorithm provides interference suppression prior to the acquisition of a direct-sequence signal. The design of the receiver front end, the DSP implementation, and the emulation of both algorithms have been performed. Emulations show increased interference suppression of at least 30 dB beyond what can be obtained from the processing gain of the direct-sequence signal. Moreover, the algorithms are effective in both far-field and near-field interference environments. The implementations use an S-Band four-antenna square monopole array with each antenna connected to a separate receiver. In one implementation, the acquisition/tracking is done via hardware, and the sampled I-Q baseband outputs of each receiver are digitally processed by the algorithm. In the other implementation, which acts as a software-defined radio, the second IF signals are sampled directly, and the respective DSP units perform acquisition/tracking and algorithm operations.